Sailing to freedom : maritime dimensions of the Underground Railroad - Walker, Timothy Dale, 1963- (University of Massachusetts Press, 2021)
"In 1858, Mary Millburn successfully made her escape from Norfolk, Virginia, to Philadelphia aboard an express steamship. Millburn's maritime route to freedom was far from uncommon. By the mid-nineteenth century, an increasing number of enslaved people had fled northward along the Atlantic seaboard. While scholarship on the Underground Railroad has focused almost exclusively on overland escape routes from the antebellum South, this groundbreaking volume expands our understanding of how freedom was achieved by sea and what the journey looked like for many African Americans. With innovative scholarship and thorough research, Sailing to Freedom highlights little-known stories and describes the less-understood maritime side of the Underground Railroad, including the impact of African Americans' paid and unpaid waterfront labor. These ten essays reconsider and contextualize how escapes were managed along the East Coast, moving from the Carolinas, Virginia, and Maryland to safe harbor in northern cities such as Philadelphia, New York, New Bedford, and Boston. In addition to the volume editor, contributors include David S. Cecelski, Elysa Engelman, Kathryn Grover, Megan Jeffreys, Cheryl Janifer LaRoche, Mirelle Luecke, Cassandra Newby-Alexander, Michael D. Thompson, and Len Travers"--